Design Of A Financial Information System Based On Embarcadero RAD STUDIO XE2 At Ino Motor Tanjungpandan - Prabowo, Brama Wahyu; Reza Firdaus (Gayaku Publisher, 2024)
This research aims to facilitate Ino Motor in entering, storing, and processing purchase, sales, and expenditure data, as well as printing financial reports. This research employed interview and observation methods. The research period spanned from May to July 2022, conducted at Dealer Ino Motor Tanjungpandan. The development of this financial information system used Embarcadero RAD Studio XE 2 as the application and Microsoft Access as the database. The development method used for this financial information system was the waterfall method, which consists of several stages: requirement, design, implementation, verification, and maintenance. To enter data into the financial information system, one must access the main menu and select the data menu. In the data menu, the administrator can input motorcycle data, supplier data, and customer data, then proceed to fill out the data and save it in the system. Afterward, the administrator can go to the transaction menu, where they can process and manage purchase, sales, and expenditure data. To print reports, the administrator can navigate to the report menu, select the desired report, and print it directly from the system.